Levels of organochlorine contaminants in natural bovine milk marketed in Mojuí dos Campos and Belterra, Brazil - Rêgo, Isabella Clarissa Vasconcelos; Cardoso, Julio César Amaral; Sacramento, José Augusto Amorim Silva do; Azevedo, Márcia Mourão Ramos; Ribeiro, Joseph Simões; Lopes, Ruy Bessa; Moura, Lucinewton Silva de; Mendes, Rosivaldo de Alcântara; Taube, Paulo Sérgio (Acta Scientiarum. Animal Sciences, 2023)
Analyzing the organochlorine pesticide (OCP) content in milk is relevantbecause it helps evaluate the quality of milk that reaches the consumer’s table and also helps identify the geographical areas where there is a high possibility of contamination. Accordingly,thispilot project was aimed at determining the extent of contamination by OCP residues and their metabolites in fresh cow’s milk in Mojuí dos Campos and Belterra, Pará, using solid-phase extraction (SPE) and gas chromatography coupled with electron capture detection (GC-ECD). The OCPs evaluated in this study weredichlorodiphenyltrichloroethane (DDT) and its metabolites (dichlorodiphenyldichloroethylene (DDE) and dichlorodiphenyldichloroethane (DDD)), hexachlorocyclohexane (HCH) (α, β, γ, and δ), endosulfanα and β, andendosulfansulfate. None of the thirty bovine milk samples analyzedshowed any contamination with OCPs.TheOCP content was within the limit of quantification of the method. The results of this study add to the existing knowledge on the quality ofbovine milk produced in these locations. However, further researchon other environmental matricesis required to confirm the results obtained in this study.